Implementation of The Remuneration System for Service Services at The Regional General Hospital of Central Kalimantan Province as a Regional Public Service Agency in The Ina-Cbg Era - Purwadhi, Purwadhi; Sibarani, Tagor; Rahim, Agus Hadian (ProBisnis : Jurnal Manajemen, 2024)
Remuneration is a demand of health workers (nakes) who work in regional hospitals, in fact, it is not uncommon to result in demonstration activities in the form of peaceful actions from health workers in government hospitals who demand especially against the hospital director that there is clarity and realization of the payment of remuneration and remuneration for these services. The purpose of this study is to identify the implementation of the Service Remuneration system, especially in the Central Kalimantan Provincial Hospital in the INA-CBG era. The method of this research is qualitative descriptive. The informants involved in this study were the Director of the Hospital, the Deputy Director of General and Finance, the Head of the Section, the Head of SMF, the Staff, certain functionalities and contract doctors. The results of the study were analyzed by the triangulation method. The results obtained in this study are planning the implementation of the remuneration system in the form of comparative studies with other hospitals, a remuneration team has not been formed and a pattern of service delivery based on position, professionalism, responsibility, and the principle of togetherness, has not used a purely performance-based remuneration system.